Sosialisasi Menanamkan Pendidikan Anti Korupsi (PAK) Di SMK Negeri 1 Selo - Subakti, Afdhoni Tri; Yasmin, Risky Nabila; Rahmaditya, Rifky Ramadhan; Sulistyowati, Arrin (Journal Of Human And Education (JAHE), 2025)
The definition of corruption is dishonest or illegal behavior, especially done by people who are always concerned with themselves. We do not realize that there are many behaviors of students who often commit corruption at school, be it corruption of class cash book money, or corruption of time. Our goal is to conduct Socialization at SMK Negeri 1 Selo so that students can avoid Corruption behavior even though there are no Corruption cases it is better for students of SMK Negeri 1 Selo to get Anti-Corruption Education socialization to form an attitude of anti-corruption values in students as an attitude to control, reduce or even overcome corruption in the form of overall efforts to encourage future generations to develop an attitude of rejection of every form of corruption.